Strategies for managing uncertainty : booms and busts in the energy industry - Marcus, Alfred A. (Alfred Allen), 1950- (Cambridge : Cambridge University Press, 2019)
All organizations must cope with future uncertainties. These uncertainties affect the strategic choices they make. They must commit scarce organizational resources to future outcomes which they have little assurance will come into being. Marcus explores how decision makers in the energy industry made choices in the face of such uncertainties, specifically examining two major uncertainties they confronted in the 2012-18 period - price volatility and climate change. Marcus tells the story of how different companies in the integrated oil and natural gas sector and in the motor vehicle sector responded to these uncertainties. In the face of these challenges, companies in the energy industry hedged their bets by staking out paradoxical or contrasting positions. On the one hand, they focused on capturing as much gain as they could from the world's current dependence on fossil fuels and on the other hand they made preparations for a future in which fossil fuels might not be the world's dominant energy source.
Machine generated contents note: Introduction: calculated wagers and hedging; Part I. The Problem: 1. Risk and uncertainty in the energy industry; 2. The management of risk and uncertainty; 3. Hedging in the energy industry; 4. Booms and busts in the energy industry; Part II. Challenges in Major Sectors: 5. The oil and natural gas sector; 6. The motor vehicle sector; 7. The electric utility sector; Part III. Oil and Natural Gas Company Strategies: 8. Strategies to try to offset plummeting prices: Exxon Mobil; 9. Strategies to try to offset plummeting prices: BP; 10. Strategies to try to offset plummeting prices: Shell; 11. Strategies to try to offset plummeting prices: Total; Part IV. Motor Vehicle Company Strategies: 12. Strategies to take advantage of plummeting prices: GM; 13. Strategies to take advantage of plummeting prices: Ford; 14. Strategies to take advantage of plummeting prices: VW; 15. Strategies to take advantage of plummeting prices: Toyota; Part V. Conclusion: 16. Oil and gas companies strategic moves 2017-18; 17. Motor vehicles companies strategic moves 2017-18; 18. Ambivalence, paradox, and hedging.
Title from publisher's bibliographic system (viewed on 13 Mar 2019).
Keywords: Uncertainty